235k views
2 votes
The steps to solve it. Unsure what step I am missing.

solve: e^(6x)=6e^(x)

The steps to solve it. Unsure what step I am missing. solve: e^(6x)=6e^(x)-example-1

1 Answer

7 votes
Solve:
e^(6x) = 6e^(x)

Taking the natural log of both sides will cancel out the left hand side, since exponentials and logarithmic functions are inverses of each other.


ln(e^(6x)) = ln(6e^(x))

Using the property, log(ab) = log(a) + log(b), we can simplify the right hand side, and the left side simply will cancel down to 6x.


6x = ln(6) + ln(e^(x))

6x = ln(6) + x

Isolate the variable to solve directly for x.

6x - x = ln(6)

5x = ln(6)


\therefore x = (ln(6))/(5)
User Matt Kline
by
6.3k points